Project Tilurium - Roman pottery from Tilurium - Šimić-Kanaet, Zrinka (2010)
The Roman pottery from Tilurium is represented by tableware (plates, platters, beakers, bowls), kitchenware (cooking pots and other items for food processing) as well as storage wessels for food and liquid.